Application of bioreactor systems for large scale production of horticultural and medicinal plants - Paek, K.Y.; Chakrabarty, D.; Hahn, E.J.
Automation of micropropagation via organogenesis or somatic embryogenesis in a bioreactor has been advanced as a possible way of reducing costs. Micropropagation by conventional techniques is typically a labour-intensive means of clonal propagation. The paper describes lower cost and less labour-intensive clonal propagation through the use of modified air-lift, bubble column, bioreactors (a balloon-type bubble bioreactor), together with temporary immersion systems for the propagation of shoots, bud-clusters and somatic embryos. Propagation of Anoectochilus, apple, Chrysanthemum, garlic, ginseng, grape, Lilium, Phalaenopsis and potato is described. In this chapter, features of bioreactors and ioreactor process design specifically for automated mass propagation of several plant crops are described, and recent research aimed at maximizing automation of the bioreactor production process is highlighted.
Keywords: BTBB; BALLOON TYPE BUBBLE BIOREACTOR; DO-DISSOLVED OXYGEN; IEDC-INDUCED EMBRYOGENIC DETERMINED CELLS; PLB-PROTOCORM-LIKE BODY; PPF-PHOTOSYNTHETIC PHOTON FLUX; STR-STIRRED TANK REACTOR